Peasants, Wars and Evil Coins: Towards a 'Monetary Turn' in Explaining the 'Revolution of 1525'. - Rössner, Philipp (German History, 2025)
Is there anything left to say about the Peasants' War of 1524/25? This article takes up that challenge by demonstrating how the 'monetary turn' evident in the later decades of the fifteenth century and early decades of the sixteenth century explains an often-overlooked item amongst peasants' complaints: the nature of their financial exploitation by feudal lords and their administrators. Such monetary concerns had featured prominently on lists of peasant grievances since the 1460s and fed into Empire-wide discourses on good governance and imperial reform. At their core, this article suggests, was the debasement and lack of the small change coins that peasants used in daily exchanges and to pay taxes and other levies. This article explores these very real monetary grievances and the challenges of righting them, generating a new thread to weave into explanations of the nature and timing of the German peasant revolt of 1524/25.